Relationship of serum elastin peptide level to single breath transfer factor for carbon monoxide in French coal miners. Issue 12 (December 1997) - Frette, C; Jacob, M P; Wei, S M; Bertrand, J P; Laurent, P; Kauffmann, F; Pham, Q T
Abstract : BACKGROUND: Clinical and epidemiological studies have given discordant results on the usefulness of the level of circulating elastin peptide (EP), a potential marker of both elastin destruction (a key phenomenon in pulmonary emphysema) and neosynthesis, for assessing structural changes in the lung extracellular matrix. The aim of the present study was to explore the relationship between levels of EP and forced expiratory volume in one second (FEV1) and single breath transfer factor for carbon monoxide (TLCO and KCO) in coal miners. METHODS: The study population comprised 227 working coal miners aged 34-50 years consisting of 75 miners heavily exposed to underground coal dust with pulmonary radiographs classified as 0/1 or 1/0 by the International Labour Office classification, 75 exposed miners with radiographs classified as normal (0/0), and 77 miners slightly exposed to coal dust with normal radiographs. The subjects answered a standardised questionnaire and performed spirometric tests and a carbon monoxide (CO) transfer test. RESULTS: No association was observed between EP levels and % predicted FEV1 (or FEV1/FVC). The level of EP increased significantly with decreased % predicted TLCO (r = -0.20). Miners in the lowest % predicted KCO quintile had higher EP levels than the rest (3.28 (1.37) vs 2.47 (1.16)). A significantly lower EP level was observed in miners with radiographs classified as 1/0 or 0/1, especially in those with round opacities, compared with miners with a normal radiograph, and in current smokers compared with the rest. CONCLUSIONS: The results of this study suggest that the level of EP may reflect some remodelling activity in emphysema and lung fibrosis.